High-Performance Reconfigurable Supercomputing Architectures. (Computer (00189162), 2007)
The article discusses field-programmable gate arrays (FPGAs) being used in computers sold by high-performance vendors in their parallel architectures. Various companies that use FPGAs are discussed including SGI's Reconfigurable Application Computing RC100, Cray's XD1, SRC Computers Inc.'s SRC-7, and Linux Networx's SS1200 accelerator. The author describes what pieces are used in the construction of the supercomputers and how they are utilized to achieve maximum performance. The benefits of each are discussed as are features they possess.